(untitled) (Al-Qamar, 2023)
Sharaf Al-Dīn Muḥammad ibn Saʿīd Al-Ṣanhājī Al-Būṣīrī, a master of Arabic rhetoric, crafted a poetic masterpiece known as "Al-Burdah." This renowned poem, titled "Al-Kawākib Al-Durriyyah Fī Madḥ Khayr Al-Bariyyah," showcases Al-Būṣīrī’s exceptional command over various rhetorical devices, including metaphor, simile, allusion, and rhyme. Simile, in particular, plays a prominent role in the poem, as Al-Būṣīrī skillfully compares the Prophet Muḥammad’s physical and moral attributes to natural phenomena like the sun, moon, and stars. Through these vivid and evocative comparisons, the greatness of the Prophet is emphasized, leaving a lasting impression on the reader’s imagination. Another noteworthy aspect of the poem is its effective use of repetition, especially in the refrain that concludes each stanza. Deliberateerate repetition reinforces the central themes of the poem and contributes to its rhythmic and melodic quality, enhancing its overall beauty. Additionally, Al-Burdah employs rhetorical questions, hyperbole, and irony to convey its message with impact and engage the reader’s attention. These rhetorical techniques, combined with the poem’s profound religious and cultural significance, have solidified its place as a beloved and enduring masterpiece of Arabic literature. This article aims to examine the artistic value and significance of the second set of 31 couplets in "Al-Qaṣīdah Al-Burdah," providing insights into the remarkable artistic status of this widely celebrated Qaṣīdah.